Grubbs–Hoveyda type catalysts bearing a dicationic N-heterocyclic carbene for biphasic olefin metathesis reactions in ionic liquids - Koy, Maximilian (Beilstein J Org Chem, 2015)
The novel dicationic metathesis catalyst [(RuCl(2)(H(2)ITapMe(2))(=CH–2-(2-PrO)-C(6)H(4)))(2+) (OTf(−))(2)] (Ru-2, H(2)ITapMe(2) = 1,3-bis(2’,6’-dimethyl-4’-trimethylammoniumphenyl)-4,5-dihydroimidazol-2-ylidene, OTf(−) = CF(3)SO(3)(−)) based on a dicationic N-heterocyclic carbene (NHC) ligand was prepared. The reactivity was tested in ring opening metathesis polymerization (ROMP) under biphasic conditions using a nonpolar organic solvent (toluene) and the ionic liquid (IL) 1-butyl-2,3-dimethylimidazolium tetrafluoroborate [BDMIM(+)][BF(4)(−)]. The structure of Ru-2 was confirmed by single crystal X-ray analysis.